The Effect of Tax Avoidance, Profitability, and Corporate Governance on Firm Value in Consumer Non-Cyclicals Sector Companies Listed on the Indonesia Stock Exchange for the 2021–2025 Period - Gian Giovania Gian; Bucek Jalu Prasetyo Arjuna; Paulus Kombo Allo Layuk (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Firm value is an important indicator that reflects investors’ confidence in a company’s performance, prospects, and sustainability. In an increasingly competitive business environment and amid growing demands for transparency, companies need to pay attention not only to their ability to generate profits but also to their tax policies and the quality of corporate governance. Therefore, research on the factors that influence firm value is important, particularly in the consumer non-cyclicals sector, which plays a strategic role in fulfilling society’s basic needs. This study aims to analyze the effect of tax avoidance, profitability, and corporate governance on firm value in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange. This study employs a quantita